Paradigm Change: A landscape-based approach as a new paradigm for Valparaiso - Seguel Medina, Cristian (Journal of Delta Urbanism, 2025)
Contemporary urbanization has positioned urban areas as pivotal in global development, with cities driving economic activity while facing critical environmental challenges. Alongside this, concerns about climatic pressures on urbanized and natural areas are evident worldwide. This paper presents a landscape-based approach as a new paradigm for urban planning and design in Valparaíso (Chile), addressing challenges posed by contemporary urbanization and climate change. Cities increasingly serve as economic hubs yet face significant environmental threats, particularly in regions like Valparaíso, which is vulnerable to wildfires, floods, and landslides due to its geography and socio-ecological fragmentation. Recent climate change impacts, exacerbated by inadequate planning and regulatory frameworks that fail to recognize hydrogeomorphological structures and socio-ecological systems, have heightened urban vulnerability and ecological degradation, leading to the loss of vital vegetation and ecosystems. This study underscores the interconnectedness of urbanization and natural systems, advocating a shift from traditional paradigms toward an adaptive landscape model. This model aims to create a healthy water system for freshwater supply, groundwater recharge, diverse ecosystems, and ecotones, integrating green/blue infrastructure, risk, and resilience strategies. The research methodology follows two approaches: first, situating the study within new paradigms that examine ecology, landscape, and infrastructure as urban-environmental articulators; second, analyzing historical urban processes that have led to Valparaíso’s current deterioration. Finally, this study discusses urban paradigms that promote coexistence between urban development and ecological preservation, ensuring a sustainable future for the city and its inhabitants.